Approximation of clogging in a leachate collection system in municipal solid waste landfill in Osecna (Northern Bohemia, Czech Republic) - Stibinger, Jakub (Waste management, 2017)
The research was focused on approximation of clogging in a leachate collection system in municipal solid waste landfill in Osecna, situated near the location Osecna, region Liberec, Northern Bohemia, Czech Republic, by analysis of numerical experiment results. To approximate the clogging of the leachate collection system after fifteen years of landfill operation (1995-2009) were successfully tested modified De Zeeuw-Hellinga transient drainage theory. This procedure allows application of the reduction factors to express clogging of the leachate collection system in Osecna landfill. The results proved that the modified De Zeeuw-Hellinga method with reduction factors can serve as a good tool for clogging approximation in a leachate collection system in Osecna landfill.
Keywords: Česká republika; chemické látky znečišťující vodu; tuhý odpad; Czech Republic; Solid Waste; odpadky - odstraňování; Water Pollutants, Chemical; skládková zařízení; Waste Disposal Facilities; Refuse Disposal